Changes of HbA1c variability after the switch to a longer‐acting insulin analog in people with type 1 diabetes. Issue 2 (7th November 2022) - Watanabe, Hirotaka; Takahara, Mitsuyoshi; Katakami, Naoto; Shimomura, Iichiro
ABSTRACT: This study investigated whether longer‐acting basal analogs (insulin degludec and insulin glargine U300) could reduce visit‐to‐visit hemoglobin A1c (HbA1c) variability in patients with type 1 diabetes. Ninety adults with type 1 diabetes for whom the basal insulin was switched to a longer‐acting insulin analog were analyzed retrospectively. The coefficient of variation of HbA1c levels (CV‐HbA1c) during the year before and after the switch was compared. The CV‐HbA1c after the switch was not significantly different from that before the switch (4.39 ± 2.24% vs 4.25 ± 2.07%; P = 0.506). The linear regression model revealed that CV‐HbA1c before the switch was independently associated with the change of CV‐HbA1c (regression coefficient per standard deviation = −0.568, P < 0.001), whereas the other variables were not (all P > 0.05). In conclusion, CV‐HbA1c remained unchanged after the switch on average, but CV‐HbA1c before the switch was associated with the decrease of CV‐HbA1c in individuals with type 1 diabetes.